Kontribusi Sektor Kreatif dalam Pembangunan Ekonomi di Provinsi Papua - Yundy Hafizrianda; Vanessa D.P. Pangke (Universitas Cenderawasih, 2024)
This study aims to analyze the potential of the creative industry sector in economic development in Papua Province. Through a quantitative approach using secondary data from the Central Statistics Agency (BPS) and literature studies, this study explores the development of the creative industry in Papua Province from 2018 to 2021, including the number of business units, workforce, capital, income, and challenges faced. The analytical methods used are descriptive statistics, panel data regression, R/C Ratio, and 4-quadrant analysis. The results of the analysis show that the creative industries that have developed in Papua Province so far, if detailed according to the KLBI (Indonesian National Economic and Trade Association), are the Ready-to-Wear Industry; Leather, Leather Goods, and Footwear Industry; Wood Processing, Wood and Cork Products, and Woven Products; Printing and Reproduction of Recorded Media; Furniture Industry; and Other Processing Industries. The trend of the creative industry in Papua over the past 10 years has always fluctuated, both in the number of business units, workforce, and income, with a significant increase in 2021, reflecting the optimism of creative industry players amidst challenges in access to capital and infrastructure. The research also found that the number of business units and revenue, both partially and simultaneously, had a very significant influence on employment. The creative apparel industry has the greatest potential in Papua Province. This is evident in its high labor absorption capacity and above-average R/C (Revenue-to-Cost) ratio. This sector is capable of absorbing a significant workforce, creating employment opportunities for many people and supporting the local economy. The policy implications of this research recommend the need for government support in the form of better access to financing, improved infrastructure, and skills training programs to strengthen the competitiveness of the creative industry sector. Thus, the creative sector can not only contribute to the regional economy but also enrich Papua's local culture and heritage.. Key Words : Creative Industry, Leading Sector, Economic Growth